2021
DOI: 10.3389/fpsyg.2021.642315
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Factors Affecting Vocabulary Development in Young South African Children

Abstract: Sociocultural influences on the development of child language skills have been widely studied, but the majority of the research findings were generated in Northern contexts. The current crosslinguistic, multisite study is the first of its kind in South Africa, considering the influence of a range of individual and sociocultural factors on expressive vocabulary size of young children. Caregivers of toddlers aged 16 to 32 months acquiring Afrikaans (n = 110), isiXhosa (n = 115), South African English (n = 105), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
1
6
1
Order By: Relevance
“…In the EGRS 2, a quarter of caregivers indicated that they never used English at home and 40% indicated that they never speak English to others (Schaefer & Kotzé, 2019). In contrast to Southwood et al (2021), we did not find an effect of school location on isiZulu/Siswati vocabulary. This may be the result of from the school sampling which included very few strictly urban schools (Kitsao-Wekulo et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the EGRS 2, a quarter of caregivers indicated that they never used English at home and 40% indicated that they never speak English to others (Schaefer & Kotzé, 2019). In contrast to Southwood et al (2021), we did not find an effect of school location on isiZulu/Siswati vocabulary. This may be the result of from the school sampling which included very few strictly urban schools (Kitsao-Wekulo et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…In line with Kitsao-Wekulo et al (2019) and Southwood et al (2021), SES did not affect vocabulary in either language in this study. Biological sex also did not affect vocabulary scores, a result that counters that of Kitsao-Wekulo et al (2019) and Mazibuko and Chimbari (2020), who found an advantage for males on their tests.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although over 30 language pairs have been investigated, most are represented in only a few studies, and there remain many languages still to be investigated (see Kidd & Garcia, 2022 (Singh et al, 2022). In South Africa, an inter-university collaboration is focused on developing CDIs for all South African languages (e.g., Southwood et al, 2021). Other efforts are working on documentation of under-studied languages (Hellwig et al, 2021) Second, the literature on parent reported vocabulary development in bilingual children has focused on production, rather than comprehension, and primarily in toddlers, rather than children under 1 ½ years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Play is considered as an educational powerful process that learning will occur spontaneously, even if an adult is not present. Play reveal children's intellectual and emotional needs and play has an educational and developmental function as it enables children to control their behavior and accept the limitations of the real world and furthers the development of the ego and a sense of reality (Southwood, White et al, 2021).…”
Section: Introductionmentioning
confidence: 99%